Pengaruh Musik Almira Berto terhadap Mood Positif Pendengar: Analisis Komentar dan Interaksi di Media Sosial - Fahmi Hamaduddin (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study analyzes the influence of Almira Berto's music on listeners' positive mood through comments and interactions on social media, specifically TikTok and Spotify. The method used is qualitative content analysis, collecting comments and interactions from both platforms. Data were analyzed by coding words that indicate a positive mood, such as “happy,” “energetic,” and “relaxed.” The results show that fans’ interactions and comments tend to contain positive words, demonstrating the music’s influence on listeners’ mood. This study contributes to the understanding of digital music psychology and fan engagement on social media.